Do fair value measurements affect accounting-based earnings quality? A literature review with a focus on corporate governance as moderator - Johannes Thesing; Patrick Velte (Journal of Business Economics, 2021)
This structured literature review of 48 archival-based studies investigates the influence of fair value measurements on earnings quality and stresses the moderating impact of corporate governance. We focus on accounting-based earnings quality measures that have several advantages for investigating agency-related earnings management behavior compared to market-based measures (e.g. value relevance studies). Fair value measurements are not restricted to specific industries, periods, circumstances, or items in our sample. Based on the applied earnings quality measure, the reviewed articles are structured into five categories: (1) earnings persistence and predictive ability, (2) discretionary accruals, (3) target beating and properties of analysts' forecasts, (4) earnings variability, and (5) other earnings quality measures. We indicate three key findings: first, fair value measurements show mixed earnings quality; second, lower-level fair value measurements decrease earnings quality; and third, corporate governance measures enhance earnings quality. After that, we deduce six research questions for future research. We show possible extensions to previous research designs in methodology and settings. Future research should also focus on corporate governance variables to a greater extent, especially compensation and board structures. Thereby, we suggest extending the neoclassical view with behavioral aspects.
Keywords: G32; G41; M41; M42; M48; 650; Fair value; Corporate governance; Audit; Earnings quality; Earnings management